Gender and Economic Growth in Tanzania : Creating Opportunities for Women - Ellis, Amanda; Blackden, Mark; Cutura, Josephine; MacCulloch, Fiona; Seebens, Holger (Washington, DC: World Bank, 2012)
The World Bank Group recognizes the critical importance of women's contribution to shared economic growth, especially in Africa. Women's important contribution to economic activity in Tanzania is well recognized: In the 2006 World Economic Forum Global Gender Gap report Tanzania was ranked number 1 globally, out of 115 countries, in terms of women's economic participation. This paper includes the following headings: gender and economic growth in Tanzania; starting and closing a business; access to land and site development; access to finance; operating a business -- taxation, infrastructure, and access to day care; labor laws -- how they affect women; access to commercial justice; access to international trade; and the way forward.